Biomass Demineralization and Pretreatment Strategies to Reduce Inhibitor Concentrations in Itaconic Acid Fermentation by Aspergillus terreus - Gregory J. Kennedy; Michael J. Bowman; Kim L. Ascherl; Nancy N. Nichols; Badal C. Saha (Biomass)
Itaconic acid (IA) is a platform chemical, derived from non-petroleum sources, produced through the fermentation of glucose by Aspergillus terreus. However, producing IA from alternative sugar sources (e.g., lignocellulose) has been shown to be problematic, requiring post-hydrolysis mitigation to allow growth and IA production by the fungus. It is well known that the side products of lignocellulosic biomass conversion to sugars act as microbial growth inhibitors. An uncommon feature of fungal organic acid fermentations is production inhibition caused by mineral ions in biomass hydrolysate after pretreatment and enzymatic hydrolysis. To minimize mineral introduction during pretreatment and hydrolysis, we determined the sources of growth and production inhibitors at each of these steps. Biomass demineralization and four pretreatment strategies were evaluated for inhibitor introduction. Dilution assays determined the approximate degree of inhibition for each hydrolysate. An ammonium hydroxide pretreatment of demineralized wheat straw presented the lowest concentration of inhibitors and concomitant lowest inhibition: subsequent fermentations produced 35 g L−1 IA from wheat straw hydrolysate (91 g L−1 sugar) without post-hydrolysis mitigation.